A multicentric survey to evaluate preclinical education in Endodontology in German‐speaking countries. (1st July 2021) - Sacha, Sabine Rosa; Sonntag, David; Burmeister, Ulrike; Rüttermann, Stefan; Gerhardt‐Szép, Susanne
Abstract: Aim: To evaluate preclinical education in Endodontology at Austrian, German and Swiss dental schools using an online survey. Methodology: An online survey divided into nine categories was sent using SurveyMonkey software to 37 dental schools, before the spread of the COVID‐19 pandemic. The questionnaire included 50 questions to evaluate preclinical endodontic education, such as faculty‐to‐student ratios, topics taught and materials used, in preclinical phantom head courses. Seven and 14 days after the first e‐mail contact, dental schools received a reminder e‐mail. After four and six weeks, the dental schools were contacted by telephone and asked to participate in the online survey. The processing time was eight weeks in total. Results: The response rate was 89%. Preclinical endodontic education at the participating dental schools differs considerably. Theory classes ranged from 1 to 70 h (15 h mean), and practical classes ranged from 3 to 78 h (39 h mean). The faculty‐to‐student ratio varied between 1:4 and 1:38 (1:15 mean). Forty‐five per cent of the dental schools had a specialist in endodontics teaching theory. Several dental microscopes were available for preclinical teaching purposes at 82% of the dental schools. The majority (82%) taught root canal preparation with rotary or reciprocating NiTi instruments. Overall, 85% of the dental schools taught lateral compaction, amongst other methods, for canal filling. Conclusion: A substantial divergence amongst the dental schools regarding the time dedicated to theory and practical instruction in Endodontology was reported. However, convergence in the use of root canal treatment techniques and materials was reported.